2007
DOI: 10.1111/j.1365-2362.2007.01854.x
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone shift circadian rhythm of blood pressure from non‐dipper to dipper type in type 2 diabetes mellitus

Abstract: The present study demonstrated that pioglitazone can restore the nocturnal BP declines in parallel to reductions in the HOMA index, suggesting that insulin resistance may play an important role in the genesis of circadian BP rhythms. TZD-based treatment may thus have the additional therapeutic advantage of reducing the risk of cardiovascular complications by transforming the circadian rhythm of BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 35 publications
(42 reference statements)
0
26
1
Order By: Relevance
“…So far, blood pressures have been measured by auscultation using devices similar to the ''ancestral'' device developed by Scipione Riva-Rocci, even in large clinical trials. However, recent evidence indicates that the office blood pressure (OBP) is significantly less reliable than measurements obtained by home blood pressure monitoring (HBPM) and ambulatory blood pressure monitoring (ABPM) for the prediction of cardiovascular events [3][4][5][6][7][8][9][10][11][12][13][14]. Therefore, HBPM or ABPM should be performed rather than measuring OBP to obtain more objective data for blood pressure management in the future.…”
Section: Introductionmentioning
confidence: 96%
“…So far, blood pressures have been measured by auscultation using devices similar to the ''ancestral'' device developed by Scipione Riva-Rocci, even in large clinical trials. However, recent evidence indicates that the office blood pressure (OBP) is significantly less reliable than measurements obtained by home blood pressure monitoring (HBPM) and ambulatory blood pressure monitoring (ABPM) for the prediction of cardiovascular events [3][4][5][6][7][8][9][10][11][12][13][14]. Therefore, HBPM or ABPM should be performed rather than measuring OBP to obtain more objective data for blood pressure management in the future.…”
Section: Introductionmentioning
confidence: 96%
“…Yang et al found that global deletion of PPAR γ abolished these rhythms even without affecting locomotor activity under regular light/dark conditions [43]. In addition, pioglitazone has been shown to transform BP from a nondipper to a dipper type in type 2 diabetic patients [44]. These findings strongly support an essential role of PPAR γ in maintaining circadian rhythms of BP and HR, which may partially explain the beneficial side effects of PPAR γ agonists in cardiovascular system.…”
Section: Pparγ and Circadian Clockmentioning
confidence: 98%
“…Importantly, observational studies from human subjects and experimental animals have demonstrated a possible role of PPARγ in organizing the diurnal rhythm of cardiovascular function. For example, in diabetic patients whose diurnal blood-pressure rhythms were dampened, pioglitazone was found to restore their rhythms [73]. Additional evidence that PPARγ might be involved in regulating the diurnal rhythm of blood pressure has also been obtained from animal studies, which demonstrated that caloric restriction in obese mice normalized the blood-pressure rhythm and increased the expression of PPARγ in the heart and aortic tissues [74].…”
Section: Acknowledgmentsmentioning
confidence: 73%